Study Short Term and Long Term Impact of Effective Real Exchange Rate on Oil Price Growth in Iran - Davari, Hamid; Kamalian, Alireza (International Journal of Energy Economics and Policy, 2017)
Exchange rate is considered as a criterion of money equivalent value for a country in compare to other countries and it reflects economic condition of that country in compare to economic status of other ones. Variation of exchange rate can be extremely effective on oil price in oil-rich countries specifically Iran. Since effects of macroeconomic variables are different in short term and long term time, in this study, short term and long term impact of effective real exchange rate on oil price growth in Iran is studied. In order to estimate long term relationship between effective real exchange rate and oil price, monthly and compiled data of OPEC were utilized from 2001-2015. Firstly, variables' durability was studied and then lack of durability Johansen differentiation and accumulation. Finally, results of the study indicated that effective real exchange rate has effect on oil price in long term while, based on BVAR, this effectiveness is not true in short term. Keywords: Exchange rate, oil price, BVAR JEL Classification: Q4